2017
DOI: 10.1017/dmp.2016.195
|View full text |Cite
|
Sign up to set email alerts
|

Earthquakes, Fuel Crisis, Power Outages, and Health Care in Nepal: Implications for the Future

Abstract: Earthquakes are a major natural calamity with pervasive effects on human life and nature. Similar effects are mimicked by man-made disasters such as fuel crises and power outages in developing countries. Natural and man-made disasters can cause intangible human suffering and often leave scars of lifelong psychosocial damage. Lessons from these disasters are frequently not implemented. The main objective of this study was to review the effects of the 2015 earthquakes, fuel crisis, and power outages on the healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 40 publications
4
43
0
Order By: Relevance
“…Similar findings were observed in the current study where many health facilities in rural areas were located in hard to reach areas, and often lacked qualified health workers, with high attrition and lack of policy supporting establishment of health care institutions in the rural regions [25,39]…”
Section: Readiness Of Public and Private Health Facilities For Ncdssupporting
confidence: 86%
See 1 more Smart Citation
“…Similar findings were observed in the current study where many health facilities in rural areas were located in hard to reach areas, and often lacked qualified health workers, with high attrition and lack of policy supporting establishment of health care institutions in the rural regions [25,39]…”
Section: Readiness Of Public and Private Health Facilities For Ncdssupporting
confidence: 86%
“…Similar findings have been found in other resource constrained settings of low-and middle-income countries (LMICs)[23,24]. In general, driven by the lack of political stability and economic constraints, LMICs face significant challenges in maintaining preparedness of health system, coverage and quality of care.One of the major challenges in Nepal's health system is the disproportionate lack of human resources, medicines, equipment and supply chain logistics in remote regions of Nepal[6, 7,25]. In addition, other factors such as patient's socio-economic status, distance to health centres, transportation,direct and indirect costs associated with attending health centres further compound the utilization of health services in rural regions of Nepal [7, 26] and resonate with other LMICs [27].…”
mentioning
confidence: 99%
“…Similar findings were observed in the current study where many health facilities in rural areas were located in hard to reach areas, and often lacked qualified health workers, with high attrition and lack of policy supporting establishment of health care institutions in the rural regions [25,39]. Such a chronic shortage of health workforce and resources in the rural regions is likely to persist and can be compounded by the transitioning federal health system of Nepal with high level of unwillingness of health care workers to serve in the rural regions [40].…”
Section: Readiness Of Public and Private Health Facilities For Ncdssupporting
confidence: 90%
“…One of the major challenges in Nepal's health system is the disproportionate lack of human resources, medicines, equipment and supply chain logistics in remote regions of Nepal [6,7,25]. In addition, other factors such as patient's socio-economic status, distance to health centres, transportation, direct and indirect costs associated with attending health centres further compound the utilization of health services in rural regions of Nepal [7,26] and resonate with other LMICs [27].…”
Section: Readiness Of Public and Private Health Facilities For Ncdsmentioning
confidence: 99%
“…One simulation model found that of the $64 billion needed to introduce 18 vaccines to 94 countries within a 10-year time frame, $38 billion would be used to support distribution and administration alone (12). Even when developing countries can access vaccines, such as those available through the Expanded Program on Immunization (EPI) and other programs (13), maintenance and monitoring of required cold-chain conditions are not guaranteed due to varying access to equipment and resources needed to maintain optimal environmental conditions (14,15). For example, during the inspection of vaccinating facilities in Cameroon, only 76% had a functional thermometer in use.…”
Section: Introductionmentioning
confidence: 99%